Multi-environments Evaluation of Zn and Fe Enhanced Bread Wheat Genotypes in Optimum Areas of Ethiopia - Dabi, Alemu; Alemu, Gadisa; Sime, Berhanu; Duga, Ruth; Geleta, Negash; Delessa, Abebe; Solomon, Tafesse; Zegaye, Habtemariam; Kasahun, Cherinet; Asnake, Dawit; Asefa, Bayisa; Getamesay, Abebe; et al. (International Journal of Bio-resource and Stress Management, 2024)
A multi-location experiment was conducted during June, 2020–October, 2021 under rainfed condition at Kulumsa, Asasa, Adet, Holeta, and Sinana Research centers, Ethiopia to evaluate the genotype-by-environment interaction effect and grain yield stability of Zn and Fe enhanced bread wheat genotypes grown. The treatments constituted 21 advanced genotypes and two standard checks were evaluated in an alpha lattice design replicated three times and data analysis was carried using R software. The results showed that genotypes and genotype x environmental interaction had a significant (p<0.001) effect on days to 50% heading, days to 90% maturity, plant height, grain yield, and 1000 kernel weight. The bread wheat lines BW172862, EBW193416, BW172864, and EBW193414 were high-yielding across most test environments, whereas genotype EBW192455 and Hidasse were low-yielding ones. From stability analysis genotypes BW172862, and EBW193416 were identified to be the most adapted bread wheat genotypes. “BW172862 produced 24.43% and 86.38% yield advantage over the standard check (Lemu) and local check (Hidasse), respectively. The second candidate genotype EBW193416 also produced 23.58% and 85.1% yield advantage over the standard check (Lemu) and local check (Hidasse), respectively. EBW193416 and BW172862 have also exhibited lower Yellow and Stem rust severity compared to others across the test environments. Thus, BW172862 and EBW193416 were selected as best parent to recycle for bread wheat population improvement in 2023 for medium agro-ecology of Ethiopia.